Reduced-Thickness-Dependent Polarized Light Transmittance of Magnetic Fluids under Longitudinal Magnetic Field. (7th September 2011) - Pu, Shengli; Bai, Xuekun; Wang, Lunwei
Abstract : The polarized light transmittance of magnetic fluids under longitudinal magnetic field (parallels the propagation direction of the incident light) is simulated theoretically. The investigated samples are with different reduced thickness (d / λ ) in a wide range. Theoretical simulations reveal that the sample reduced thickness has a significant influence on the polarized light transmittance. The thin and thick samples have distinctly different dependence of polarized light transmittance on magnetic field strength. Based on the reduced-thickness- and magnetic-field-dependent polarized light transmittance, several magnetic-fluid-based photonic devices are proposed and discussed.